Characteristics of Hemangioma Patient in Palembang - Eka Kurniawan Perangin-Angin; Mufida Muzakkie (Sriwijaya Journal of Surgery, 2021)
Introduction: Hemangioma is a form of vascular anomaly that has various characteristics. Characteristics data, region, size of lesion, complications, and choice of treatment both operative and non-operative in hemangioma patients, especially at the RSUP Dr. Mohammad Hoesin, Palembang. This study aims to collect data and evaluate it. Methods: This study used secondary data which is medical records of all hemangioma cases treated at RSUP Dr. Mohammad Hoesin Palembang on January 1, 2019 to December 31, 2019. Data analysis used descriptive analysis, where the data that has been collected will be grouped and presented in the form of a frequency distribution table for each characteristic. Results: There were 61 medical records that meet the study criteria. The age at diagnosis was 2 (range 0-8) weeks. The number of female patients (n = 34; 55.74%) was found to be more than men (n = 27; 44.26%). Infantile hemangiomas (n = 39; 63.9%) were found to be more common than congenital hemangiomas (n = 22; 36.1%). Most of the hemangiomas were in the face (n = 36; 59%). The median size of hemangioma lesions in this study was 3 (range 0.5-10) cm. There were 18 hemangioma lesions that had complications (29.5%). The majority of hemangioma patients underwent operative management (n = 47; 77%), others underwent non-operative management (n = 14; 23%). Conclusion: Hemangiomas are found commonly in female patients. The location of the lesion is predominantly in the facial area. Nearly a third of hemangioma lesions have complications with the most common complication were ulcers. Hemangioma management was dominated by operative management which may be associated with a large number of hemangioma lesions in sensitive locations and complications.